Diversity and Bionomics of Sandflies (Diptera: Psychodidae) of an Endemic Focus of Cutaneous Leishmaniasis in Zagora Province, Southeast of Morocco. (23rd January 2021) - Al-Koleeby, Zalalham; El Aboudi, Ahmed; Aboulfadl, Souhail; Faraj, Chafika
Abstract : The diversity and seasonality for sandflies were studied in 2019 at a focus of zoonotic cutaneous leishmaniasis in Zagora province, southern Morocco. Standardized sampling with CDC light traps was used. A total of 4504 sandflies (4024 Phlebotomus and 480 Sergentomyia ) was collected during the study period. Seven species belonging to genus Phlebotomus and six species of genus Sergentomyia were identified. The most abundant species were Ph. papatasi (33.6%) and Ph. longicuspis (25.7%), highlighting the risk for local disease transmission foci. The seasonal activity of sandflies extended from April to November, showing two peaks, one in June-July and one, less important, in late-September-October. Abundance was highest during the months May, June, and July and lowest in August, September, and October. Results of this study provide important baseline data for planning control interventions.